Les lesbianaires. (Bruxelles : Centre de documentation et de recherches sur le lesbianisme radical, 1983)
Fonds Suzan Daniel (FSD)
Periodiciteit : ?
Redactie : 1, rue H. Richir, 1030 Bruxelles
Frans
Periodiek